Assessment of Maxillary Premolar Root Position Within the Alveolar Bone Using Cone Beam Computed Tomography: Cone Beam Computed Tomography Assessment of Maxillary Premolar Roots - Maqbool, Maha; Danyal, Ahmad; Manzoor, Usman; Anjum, Naveed Abbas; Khalid, Naima; Khattak, Muhammad Usman (Pakistan Journal of Health Sciences, 2025)
The location of maxillary premolars with respect to the alveolar bone and maxillary sinus is critical for treatments like extractions and implantation. CBCT imaging provides extensive information on root placement, sinus proximity, and buccal bone dimensions, enabling proper diagnosis and treatment planning. Objectives: To assess the position of the maxillary premolars’ roots within the alveolar apparatus and their relationship to the maxillary sinus using cone-beam computed tomography. Methods: This is a cross-sectional descriptive study that included CBCT images of 105 patients with 411 maxillary premolars were viewed retrospectively over a period of six months. After obtaining permission from the institutional ethical review committee, each pair of premolars was observed on either side of the mouth. Each exhibited a distinct association between its root tip and the sinus floor, categorized into four different types. The roots were also variable in the alveolar housing and were either buccal, middle, or palatally placed. Results: In our study, the majority of maxillary first premolars had roots positioned away from the sinus floor, with root angulation predominantly directed toward the buccal side. In contrast, most second premolars exhibited roots located close to or extending into the sinus floor, with their roots generally positioned centrally within the alveolar bone. Conclusions: Maxillary first premolars have weaker buccal bone, whereas second premolars are more affected by sinus proximity during implant insertion operations. Given these specific anatomical obstacles, CBCT imaging is recommended for accurate diagnosis and effective implant design.